A SYSTEMATIC LITERATURE REVIEW OF ERM, CORPORATE GOVERNANCE, INTERNAL CONTROL, AND SUSTAINABILITY REPORTING ON ENTERPRISE VALUE - Rahmi, Amelia; Widyastuti, Tri; Darmansyah, Darmansyah (Universitas Pakuan, 2025)
ABSTRACTThis study aims to analyze the determinants of firm value through a systematic literature review focusing on corporate governance, risk management, internal control, and sustainability reporting. The data for this study are articles from indexed journals with firm value as the dependent variable. Based on 67 empirical articles published between 2015 and 2025, this review synthesizes recent findings to assess how financial and non-financial mechanisms contribute to firm valuation across institutional contexts. The data were analyzed using the systematic literature review (SLR) method. The results reveal that corporate governance—specifically board independence, ownership structure, and audit committee effectiveness—are the most widely studied determinants. Risk management and sustainability reporting are increasingly studied due to their strategic signaling and stakeholder engagement roles, while internal control is less explored despite its relevance for reporting reliability and investor confidence. This study contributes by offering a structured synthesis and proposing future research directions to strengthen theoretical and methodological approaches in firm value research.ABSTRAKPenelitian ini bertujuan untuk menganalisis determinan dari nilai perusahaan melalui tinjauan literatur sistematis dengan fokus pada tata kelola perusahaan, manajemen risiko, pengendalian internal, dan pelaporan keberlanjutan. Data penelitian ini adalah artikel-artikel dari jurnal terindeks dengan nilai Perusahaan sebagai variabel terikatnya. Berdasarkan 67 artikel empiris yang diterbitkan antara tahun 2015 dan 2025, tinjauan ini mensintesiskan temuan terbaru untuk menilai bagaimana mekanisme keuangan dan non-keuangan berkontribusi pada penilaian perusahaan di berbagai konteks kelembagaan. Data dianalisis menggunakan metode systematic literature review (SLR). Hasil penelitian mengungkapkan bahwa tata kelola perusahaan—khususnya independensi dewan, struktur kepemilikan, dan efektivitas komite audit—menjadi determinan yang paling banyak diteliti. Manajemen risiko dan pelaporan keberlanjutan semakin banyak diteliti karena peran pensinyalan strategis dan keterlibatan pemangku kepentingan, sementara pengendalian internal kurang dieksplorasi meskipun relevansinya untuk keandalan pelaporan dan kepercayaan investor. Studi ini berkontribusi dengan menawarkan sintesis terstruktur dan mengusulkan arah penelitian masa depan untuk memperkuat pendekatan teoritis dan metodologis dalam penelitian nilai perusahaan.